The state of development of artistic and creative abilities of students in practical decorative arts classes in modern educational practice (Journal of Pedagogical Inventions and Practices, 2022)
The system of artistic education and upbringing can be understood only as an immanent repetition of the needs of the social organism from a certain model of society. Only through the mechanism of artistic education, the restoration of humanity's "self" (Hegel), the purposeful development of creative abilities by translating the external structures of culture (social norms, attitudes, tastes, needs) into the internal stimuli of a person's behavior. development can be carried out, which includes the unity of the individual's aesthetic beliefs. its intuitive directions and its manifestation in all forms of artistic activity.